2012
DOI: 10.1016/j.ijgo.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of unintended pregnancy after ultrasound‐guided high‐intensity focused ultrasound ablation of uterine fibroids

Abstract: Pregnancy within 1 year after USgHIFU ablation of uterine fibroids appears safe; however, large scale studies are required to confirm these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…Pregnancy was continued to full term in 7 women, and all births were given via cesarean delivery without any complications. Fifteen women were chosen to undergo an induced abortion, and 2 women experienced a spontaneous abortion [11]. Although the preliminary pregnancy experience of HIFU is encouraging, this procedure must be approached with caution because a complication that causes maternal or fetal morbidity can be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy was continued to full term in 7 women, and all births were given via cesarean delivery without any complications. Fifteen women were chosen to undergo an induced abortion, and 2 women experienced a spontaneous abortion [11]. Although the preliminary pregnancy experience of HIFU is encouraging, this procedure must be approached with caution because a complication that causes maternal or fetal morbidity can be significant.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of HIFU in the treatment of benign uterine tumors has been confirmed in multiple clinical studies 3335 , and HIFU has been recommended as a treatment option to reduce the symptoms of uterine fibroids 36 . However, there is little data available about pregnancy outcomes after HIFU, although there have been reports that indicate pregnancy is safe one year after HIFU treatment 37 . The enrollment criteria set for early clinical investigations of HIFU generally required that patients were not intending to conceive in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Wang et al [2] reported that ultrasound-guided ultrasound ablation was safe and effective in treating uterine fibroids. With the advancement of imaging monitoring technology and key ultrasound ablation techniques, a viable treatment protocol and doctor training scheme have gradually taken shape after years of clinical research and testing [3][4][5][6][7]. Since July 2006, ultrasound ablation for uterine fibroids and adenomyosis under conscious sedation has been applied in many clinical centers in China, and has even become the first-line therapy for patients in some hospitals [8,9].…”
Section: Introductionmentioning
confidence: 99%